THE EFFECT OF PRACTICUM LEARNING BASED AUDIOVISUAL ON STUDENTS LEARNING OUTCOMES - Indrawati, Cicilia Dyah S. (Efisiensi : Kajian Ilmu Administrasi, 2021)
Abstract: The Effect Of Practicum Learning Based Audiovisual On Students Learning Outcomes. This study aims to test the effectiveness of the application of audio-visual based learning media in an effort to improve student learning outcomes at vocational secondary school. This study used a quasi-experimental research strategy with a pretest-posttest control group design. Quasi-experimental research was carried out in vocational high schools in the city of Surakarta. Respondents in this study were likely 230 students who were categorized into the control group and the experimental group. The results of this study indicate the effectiveness of the application of audio-visual based learning media to improve learning outcomes effectively. This effectiveness can be proven by an increase in the mean score of the pretest and posttest scores between the control group and the experimental group. This is evidenced by the results of the independent t-test which shows significant evidence of student learning outcomes in the control group and the experimental group. Based on the research results, the use of audiovisual learning media can help students gain experiences that can be used in the world of work later.Keyword: Learning Media, Audio Visual, Learning, Learning Outcomes, Vocational Secondary SchoolÂ Abstrak: Pengaruh Pembelajaran Praktikum Berbasis Audiovisual Terhadap Hasil Belajar Siswa.Â  Penelitian ini bertujuan untuk menguji keefektifan penerapan media pembelajaran berbasis audio visual dalam upaya meningkatkan hasil belajar siswa di SMK. Penelitian ini menggunakan strategi penelitian eksperimental semu dengan desain control group pretest-posttest. Penelitian eksperimental semu dilakukan di sekolah menengah kejuruan di kota Surakarta. Responden pada penelitian ini berjumlah 230 siswa yang dikategorikan ke dalam kelompok kontrol dan kelompok eksperimen. Hasil penelitian ini menunjukkan keefektifan penerapan media pembelajaran berbasis audio visual dapat meningkatkan hasil belajar siswa secara efektif. Keefektifan tersebut dapat dibuktikan dengan adanya peningkatan nilai rata-rata skor pretes dan skor postes antara kelompok kontrol dan kelompok eksperimen. Hal ini dibuktikan dengan hasil uji-t independen yang menunjukkan perbedaan yang signifikan hasil belajar siswa pada kelompok kontrol dan kelompok eksperimen. Berdasarkan hasil penelitian, penggunaan media pembelajaran audiovisual dapat membantu siswa mendapatkan pengalaman yang bisa digunakan dalam dunia kerja nanti.Kata Kunci : Media Pembelajaran, Audio Visual, Pembelajaran, Hasil Belajar, SMK